Sensitive cell viability assay for use in drug screens and for studying the mechanism of action of drugs in Dictyostelium discoideum. (November 2006) - Min, Junxia; Sridevi, Priya; Alexander, Stephen; Alexander, Hannah
In order to increase the effectiveness of Dictyostelium discoideum as a lead genetic model for drug discovery, a luminescence-based assay has been adapted and standardized for sensitive and rapid cell viability measurements. The applicability of the assay was demonstrated by measuring the cytotoxicity of several drugs in wild-type and mutant cells. The robustness and ease of the assay demonstrate that it can be used in high-throughput applications such as drug or mutant screens. Conclusions from these studies are applicable to evaluating cell viability assays in other systems as well.